Pyruvate imbalance mediates metabolic reprogramming and mimics lifespan extension by dietary restriction in Caenorhabditis elegans - Mouchiroud, Laurent; Molin, Laurent; Kasturi, Prasad; Triba, Mohamed N.; Dumas, Marc Emmanuel; Wilson, Marieangela C.; Halestrap, Andrew P.; Roussel, Damien; Masse, Ingrid; Dallière, Nicolas; Ségalat, Laurent; Billaud, Marc; et al. (Aging cell, 2011)
Summary Dietary restriction (DR) is the most universal intervention known to extend animal lifespan. DR also prevents tumor development in mammals, and this effect requires the tumor suppressor PTEN. However, the metabolic and cellular processes that underly the beneficial effects of DR are poorly understood. We identified slcf‐1 in an RNAi screen for genes that extend Caenorhabditis elegans lifespan in a PTEN/daf‐18‐dependent manner. We showed that slcf‐1 mutation, which increases average lifespan by 40%, mimics DR in worms fed ad libitum. An NMR‐based metabolomic characterization of slcf‐1 mutants revealed lower lipid levels compared to wild‐type animals, as expected for dietary‐restricted animals, but also higher pyruvate content. Epistasis experiments and metabolic measurements support a model in which the long lifespan of slcf‐1 mutants relies on increased mitochondrial pyruvate metabolism coupled to an adaptive response to oxidative stress. This response requires DAF‐18/PTEN and the previously identified DR effectors PHA‐4/FOXA, HSF‐1/HSF1, SIR‐2.1/SIRT‐1, and AMPK/AAK‐2. Overall, our data show that pyruvate homeostasis plays a central role in lifespan control in C. elegans and that the beneficial effects of DR results from a hormetic mechanism involving the mitochondria. Analysis of the SLCF‐1 protein sequence predicts that slcf‐1 encodes a plasma membrane transporter belonging to the conserved monocarboxylate transporter family. These findings suggest that inhibition of this transporter homolog in mammals might also promote a DR response.